Comparison of ixekizumab with etanercept or placebo in moderate-to-severe psoriasis (UNCOVER-2 and UNCOVER-3): results from two phase 3 randomised trials. Issue 9993 (8th August 2015) - Griffiths, Christopher E M; Reich, Kristian; Lebwohl, Mark; van de Kerkhof, Peter; Paul, Carle; Menter, Alan; Cameron, Gregory S; Erickson, Janelle; Zhang, Lu; Secrest, Roberta J; Ball, Susan; Braun, Daniel K; et al.
Summary: Background: Ixekizumab is a humanised monoclonal antibody against the proinflammatory cytokine interleukin 17A. We report two studies of ixekizumab compared with placebo or etanercept to assess the safety and efficacy of specifically targeting interleukin 17A in patients with widespread moderate-to-severe psoriasis. Methods: In two prospective, double-blind, multicentre, phase 3 studies (UNCOVER-2 and UNCOVER-3), eligible patients were aged 18 years or older, had a confirmed diagnosis of chronic plaque psoriasis at least 6 months before baseline (randomisation), 10% or greater body-surface area involvement at both screening and baseline visits, at least a moderate clinical severity as measured by a static physician global assessment (sPGA) score of 3 or more, and a psoriasis area and severity index (PASI) score of 12. Participants were randomly assigned (1:2:2:2) by computer-generated random sequence with an interactive voice response system to receive subcutaneous placebo, etanercept (50 mg twice weekly), or one injection of 80 mg ixekizumab every 2 weeks, or every 4 weeks after a 160 mg starting dose. Blinding was maintained with a double-dummy design. Coprimary efficacy endpoints were proportions of patients achieving sPGA score 0 or 1 and 75% or greater improvement in PASI at week 12. Analysis was by intention to treat. These trials are registered with ClinicalTrials.gov, numbers NCT01597245 and NCT01646177 . Findings: Between May 30, 2012, and Dec 30, 2013, 1224 patients in UNCOVER-2 were randomly assigned to receive subcutaneous placebo (n=168), etanercept (n=358), or ixekizumab every 2 weeks (n=351) or every 4 weeks (n=347); between Aug 11, 2012, and Feb 27, 2014, 1346 patients in UNCOVER-3 were randomly assigned to receive placebo (n=193), etanercept (n=382), ixekizumab every 2 weeks (n=385), or ixekizumab every 4 weeks (n=386). At week 12, both primary endpoints were met in both studies. For UNCOVER-2 and UNCOVER-3 respectively, in the ixekizumab every 2 weeks group, PASI 75 was achieved by 315 (response rate 89·7%; [effect size 87·4% (97·5% CI 82·9–91·8) vs placebo; 48·1% (41·2–55·0) vs etanercept]) and 336 (87·3%; [80·0% (74·4–85·7) vs placebo; 33·9% (27·0–40·7) vs etanercept]) patients; in the ixekizumab every 4 weeks group, by 269 (77·5%; [75·1% (69·5–80·8) vs placebo; 35·9% (28·2–43·6) vs etanercept]) and 325 (84·2%; [76·9% (71·0–82·8) vs placebo; 30·8% (23·7–37·9) vs etanercept]) patients; in the placebo group, by four (2·4%) and 14 (7·3%) patients; and in the etanercept group by 149 (41·6%) and 204 (53·4%) patients (all p<0·0001 vs placebo or etanercept). In the ixekizumab every 2 weeks group, sPGA 0/1 was achieved by 292 (response rate 83·2%; [effect size 80·8% (97·5% CI 75·6–86·0) vs placebo; 47·2% (39·9–54·4) vs etanercept]) and 310 (80·5%; [73·8% (67·7–79·9) vs placebo; 38·9% (31·7–46·1) vs etanercept]) patients; in the ixekizumab every 4 weeks group by 253 (72·9%; [70·5% (64·6–76·5) vs placebo; 36·9% (29·1–44·7) vs etanercept]) and 291 (75·4%; [68·7% (62·3–75·0) vs placebo; 33·8% (26·3–41·3) vs etanercept]) patients; in the placebo group by four (2·4%) and 13 (6·7%) patients; and in the etanercept group by 129 (36·0%) and 159 (41·6%) patients (all p<0·0001 vs placebo or etanercept). In combined studies, serious adverse events were reported in 14 (1·9%) of 734 patients given ixekizumab every 2 weeks, 14 (1·9%) of 729 given ixekizumab every 4 weeks, seven (1·9%) of 360 given placebo, and 14 (1·9%) of 739 given etanercept; no deaths were noted. Interpretation: Both ixekizumab dose regimens had greater efficacy than placebo and etanercept over 12 weeks in two independent studies. These studies show that selectively neutralising interleukin 17A with a high affinity antibody potentially gives patients with psoriasis a new and effective biological therapy option. Funding: Eli Lilly and Co.